2012
DOI: 10.1029/2011jd015858
|View full text |Cite
|
Sign up to set email alerts
|

Using scattering calculations to compare MODIS retrievals of thin cirrus optical properties with SAM solar disk and aureole radiance measurements

Abstract: Scattering calculations for optically thin cirrus clouds based on retrievals of optical thickness and effective particle size from NASA's Moderate Resolution Imaging Spectroradiometer (MODIS) on Terra and Aqua are compared with solar disk radiance and aureole measurements from Visidyne's Sun and Aureole Measurement (SAM) instrument. In the four examples presented, the calculated solar disk radiance differs from the measurement by a factor ranging from 2 to 8. The shape of the aureole radiance profile also diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 28 publications
3
19
1
Order By: Relevance
“…Further, τ c tends to be larger than that reported by the SAM. This is in line with DeVore et al (2012), who found that the τ SAM needs to be corrected upward to account for forward scattering of ice crystals. The simulated radiances are compared with the selected SAM measurements in Figs.…”
Section: Summary Of Sensitivity Testssupporting
confidence: 49%
See 3 more Smart Citations
“…Further, τ c tends to be larger than that reported by the SAM. This is in line with DeVore et al (2012), who found that the τ SAM needs to be corrected upward to account for forward scattering of ice crystals. The simulated radiances are compared with the selected SAM measurements in Figs.…”
Section: Summary Of Sensitivity Testssupporting
confidence: 49%
“…The impacts on near-forward scattered radiation due to ice crystal roughness and habit have also been considered (DeVore et al, 2012;Segal-Rosenheimer et al, 2013;Reinhardt et al, 2014). However, the present study extends the knowledge gained in previous research (DeVore et al, 2009(DeVore et al, , 2012Segal-Rosenheimer et al, 2013;Wilbert et al, 2013;Reinhardt, 2013;Reinhardt et al, 2014) as we simulate in detail the angular distribution of phase function and radiances instead of circumsolar irradiances integrated over some angular range (as in Reinhardt et al, 2014). The potential applications of these results include remote sensing of optical thickness, ice cloud properties based on the radiance field near the sun, and the design of concentrating solar energy applications.…”
Section: Summary Of Sensitivity Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ice clouds consist almost exclusively of non-spherical ice crystals with various shapes (i.e., habits) and sizes (e.g., Liou, 1986). To determine the influences of ice clouds on solar and infrared radiation as required for numerical models and remote sensing retrievals, knowledge of single-scattering properties of ice crystals is required (e.g., Fu, 1996Fu, , 2007McFarquhar et al, 2002;Baum et al, 2011;Baran, 2012;DeVore et al, 2012;Yang et al, 2013;Yi et al, 2013;Um and McFarquhar, 2013;Cole et al, 2014;van Diedenhoven et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%